2021
DOI: 10.3390/ijerph18041595
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D Receptor Polymorphisms (BsmI and FokI) and Glycemic Control among Patients with Type 2 Diabetes

Abstract: (1) Background: Several studies have suggested that the vitamin D receptor (VDR) gene plays a role in type 2 diabetes mellitus (T2DM) susceptibility. Nonetheless, the association between T2DM and VDR polymorphisms remains inconclusive. We determined the genotype of VDR rs1544410 (BsmI) and rs2228570 (FokI) polymorphisms among Malaysian patients with T2DM and their association with glycemic control factors (vitamin D levels, calcium, magnesium, and phosphate). (2) Methods: A total of 189 participants comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The prevalence of vitamin D deficiency is attributed to weather, clothing, lifestyle, dietary intake, age, gender, susceptibility to metabolic syndrome, and genetic inheritance. All these factors can affect the bioavailability of vitamin D. 12 Vitamin D is a pleiotropic steroid hormone that can exert various effects by binding to its specific receptor, the Vitamin D receptor (VDR). VDRs are present in over 38 tissues: kidney, osteoblasts, T and B lymphocytes, keratinocytes, small intestine, prostate, gonads, bone, pancreatic islets, hair follicle, ovary, placenta, uterus, and colon.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of vitamin D deficiency is attributed to weather, clothing, lifestyle, dietary intake, age, gender, susceptibility to metabolic syndrome, and genetic inheritance. All these factors can affect the bioavailability of vitamin D. 12 Vitamin D is a pleiotropic steroid hormone that can exert various effects by binding to its specific receptor, the Vitamin D receptor (VDR). VDRs are present in over 38 tissues: kidney, osteoblasts, T and B lymphocytes, keratinocytes, small intestine, prostate, gonads, bone, pancreatic islets, hair follicle, ovary, placenta, uterus, and colon.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D and magnesium levels were found to be significantly lower among T2DM cases (12.29 ng/mL + 2.32 ng/mL and 1.60 mg/dL + 0.59 mg/dL) compared with healthy controls (19.55 ng/mL + 0.50 ng/mL and 3.36 mg/dL + 0.15 mg/dL) in a study by Gandhe et al [ 4 ]. This finding was supported by a study on diabetes patients which showed that those with poor glycemic control had significantly lower mean vitamin D and serum magnesium levels than those with good glycemic control[ 5 ]. Moreover, Ismail et al [ 45 ] reported that a hypomagnesemia of 0.88 mmol/L ± 0.10 mmol/L was commonly observed in the poor glycemic control group, while patients with good glycemic control had a higher magnesium level of 0.94 mmol/L ± 0.10 mmol/L.…”
Section: Association Of Vitamin D and Magnesium In Insulin Sensitivit...mentioning
confidence: 67%
“…Magnesium can be considered a neglected analyte in the monitoring of patients with diabetes in general wards or outpatient departments. However, several studies have shown that magnesium significantly promotes insulin secretion and action[ 4 , 5 ]. Magnesium is important for the proper functioning of various metabolic pathways and ion channels in pancreatic cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individuals with T2D with poor glycemic control were characterized by a higher BMI compared to individuals with good glycemic control with T2D and healthy volunteers (mean BMI (kg/m 2 ): 29.4 AE 5.9 vs. 27.9 AE 5.2 and 26.4 AE 4.5, P ¼ 0.007). This observation suggests that the rs2228570 polymorphism may be related to the development of obesity in non-T2D subjects [30].…”
Section: Andandmentioning
confidence: 84%